2012
DOI: 10.1111/j.1447-0756.2011.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on sexual and reproductive health behaviors of unmarried female migrants in China

Abstract: This study revealed that the unmarried female migrant was one of the most vulnerable groups concerning SRH. In some policy reforms, appropriate and cost-effective SRH services should be provided for these migrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
(45 reference statements)
2
20
2
Order By: Relevance
“…Research indicates that most female migrants migrate to metropolitan cities before marriage, when they are between 15–34 years old [5,12,17,18,19]. In China the Hukou system, which isolates rural from urban citizens, makes it difficult for rural-urban female migrants to access SRH services in the cities [5,7,17,18]. According to family planning agencies in China, the SRH service mainly targets married females and unmarried females are excluded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that most female migrants migrate to metropolitan cities before marriage, when they are between 15–34 years old [5,12,17,18,19]. In China the Hukou system, which isolates rural from urban citizens, makes it difficult for rural-urban female migrants to access SRH services in the cities [5,7,17,18]. According to family planning agencies in China, the SRH service mainly targets married females and unmarried females are excluded.…”
Section: Introductionmentioning
confidence: 99%
“…However, female migrants often hold open attitudes to premarital sex [3,15,19,20,21,22]. Unsafe sex leads to unintended pregnancy, abortions, pregnancy-related syndromes, and infectious diseases [17,23]. One study of 1,600 females in China undergoing abortion found 72.9% were migrants and 77.4% were unmarried [24].…”
Section: Introductionmentioning
confidence: 99%
“…Migrants are recognized as a high risk population for HIV and other STIs in China, and studies have shown that migrants are more likely to engage in health risk behaviors compared with non-migrants in urban China (Anderson, Qingsi, Hua, & Jianfeng, 2003; Chen, Peeling, Yin, & Mabey, 2011; He et al, 2012; Yang, Derlega, & Luo, 2007). Of the 5,635 HIV/AIDS cases reported in Beijing in 2008, 75% were internal migrants, 21% were city residents, and 4% were foreigners (Kaiser Health News, 2008).…”
mentioning
confidence: 99%
“…Previous literature has suggested that young female migrants face high risk for HIV due to a lack of knowledge related to sexual health, limited skills for practicing safer sex and low awareness and use of reproductive health services in their native rural settings (Tu et al, 2004;Liu et al, 2011aLiu et al, , 2011bMantell et al, 2011;He et al, 2012;Lu et al, 2012). Furthermore, compared with their male counterparts and urban citizens, female rural-to-urban migrants face greater social and cultural vulnerability and gender-related inequalities, such as unequal work opportunities, low socioeconomic status and lack of social support (Mou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, female migrants in China are frequently undereducated and underprepared for the increased opportunities to engage in sexual behavior that are available to them in urban settings (Huang et al, 2014). In the absence of skills, knowledge and services to promote sexual health, female migrants who relocate to large urban centers may experience risk for a range of health consequences, including unwanted pregnancy, unsafe termination of pregnancy and sexually transmitted infections (STIs) Yi et al, 2010;He et al, 2012). Some research has contrasted the more permissive norms related to premarital sex in large urban contexts versus norms in rural settings, which might also contribute to health risk behaviors among rural-to-urban migrants .…”
Section: Introductionmentioning
confidence: 99%